New Immunological Markers of Thromboembolic and Hemorrhagic Complications after Coronary Artery Bypass Grafting - Shkorik, Elena Valeryevna (Asian Journal of Pharmaceutics (AJP), 2018)
Aim and Scope: A total of 125 patients suffering from ischemic heart disease (IHD) were examined before and after coronary artery bypass grafting (CABG), there were 79 males and 46 females aged 45â€“74 years among them. Study blood samplings were performed a day before and then on the 1st, 3rd, 7th, and 12th day after the surgery. Material and Methods: Intra- and inter-group differences were estimated with Mannâ€“Whitney U-test, Spearmanâ€™s rank correlation and Ï‡2 test using application software SPSS v.16. Differences between parameters in case of deviation from null hypothesis and level of significance P < 0.05 were considered to be statistically significant. Result and Discussion: The levels of tumor necrosis factor-Î± (TNF-Î±) (Ï‡2 = 4.28, Ð < 0.05, AUC = 0.91), interleukin (IL)-10 (Ï‡2 = 3.97, P < 0.05, AUC = 0.829), and matrix metalloproteinases (MMP)-1 (Ï‡2 = 6.66, Ð < 0.01, AUC = 0.963) were defined to be early and excessively increased before CABG and in early postsurgical period in patients with post-operative thromboembolic complications, suggesting the patients with IHD have a high risk of the complications mentioned above after CABG surgery. The association of TNF-Î± hyperproduction (above 30 pg/ml) on the 1st day after CABG and hemorrhagic complications development in patients after CABG was revealed (Ï‡2 = 4.0, P < 0.05, AUC = 0.776). Conclusion: The maximum increasing of IL-6 level inpatients of all examined groups was present immediately after surgery, which was caused by surgical injury. The analysis of MMP-8 and MMP-9 did not reveal a correlation between their increased levels and the presence of complications in the patients after the surgery. The expression of the first tissue inhibitor of metalloproteinases was moderately increased in patients of all groups with no significant difference in its levels between the groups